Information delayed is justice denied : lengthy procedures deny the right to access information = Kašnjenje informacije je nedostatak pravde : dugačke procedure sprječavaju pravo na pristup informaciji - Toplak, Jurij (Array, 2019)
European Court of Human Rights ruled in 2016 that the European Convention on Human Rights includes a right to access information held by public authorities. While according to international documents the procedures for accessing information should be ‘rapid’, the courts have yet to rule on what ‘rapid’ means and when the procedures are so long that they violate rights of those asking for information. This article analyses the length of proceedings in access to information cases in Slovenia and Croatia. It shows that these two countries do not have a system of effective protection of rights because the authorities can easily delay disclosure of information for several years. It argues that lengthy procedures violate the right to access the information and the freedom of expression. It then presents solutions for improving access to information procedures in order for them to become ‘rapid’